Development of Hedgehog Pathway Inhibitors (HPI) in Treatment of Cancer - Pramanik, Dipankar (Current Chemical Biology, 2014)
Activated hedgehog signaling (Hh) cascade was first found in basal cell carcinoma but with time it has been found in other major cancer types including medulloblastoma (MB), pancreatic cancer, small cell lung cancer, liver cancer, leukemia etc. Small molecule antagonists of Hh pathway were developed to block either Hh ligands or Smoothened (Smo), a transmembrane receptor that controls Gli based downstream signaling cascades of Hh pathway. Among many Smo inhibitors like naturally occurring cyclopamine or synthetic small molecule IPI-926, GDC-0449, LDE-225, GANTs etc few small molecules are in clinical trial, and one small molecule GDC-0449 has been approved by FDA. Limitation of using Smo antagonists is due to rapid mutation in Smo itself and hence the new generation Hh antogonists like HPI-1 or HPI-2 have been developed which are capable of bypassing Smo and attacking downstream effector Gli1 directly and hence the major activated Hh pathway effectors or entire Hh signaling are suppressed. In this review, we will discuss the development of different small molecule inhibitors of Hh pathway to treat cancer.
Keywords: Smoothened